Successful combination of local flaps for large palatal fistula closure. (5th May 2015) - Perry, J.; Bhopal, S.; Bharadwaj, G.; O'Regan, B.
Abstract: The closure of large palatal fistulae may challenge oral and maxillofacial surgeons especially when considering subsequent prosthetic requirements. Surgical procedures used to reconstruct palatal defects include prostheses, local flaps, distant flaps, bone grafting and allografts. We present a case of successful closure of a large post‐resection palatal fistula using a combination of three established techniques. Closure of the superior naso‐antral layer was completed using Fickling's inkwell technique. The resultant large defect was closed using a 'tadpole' rotational palatal flap combined with a buccal fat pad advancement to secure the unsupported lateral aspect of the rotation flap and remaining denuded bone of the left hard palate. The fistula remains closed four years after surgery. This report demonstrates the effective combination of three local intra‐oral flaps as a single‐stage, low‐risk method of closing a large palatal fistula.